Screening of biological activities of Hammada elegans Botsch extracts - asseli brahim; DJERIDANE Amar (My University, 2021)
The present work was carried out to study the antioxidant capacities in vitro systems, and to evaluate for the first time the in vivo anti-inflammatory, anti-diabetic and acute toxicity properties of four extracts of aerial parts of Hammada elegans Botsch. The evaluation of the total phenolic content reveals the presence of interesting amounts of polyphenols. The highest content is found in the aqueous extract (2.560 ± 0.008 mg GAE/g dw). The quantification of flavonoids shows that the aqueous extract has the best content (0.275 ± 0.001 mg QE/g dw). Also, the quantification of tannins led us to conclude that this plant is rich in tannins. Evaluation of the antioxidant capacity by the four chemical assays showed that the aqueous extract exhibited the highest antioxidant capacities compared to the other extracts and standards. Its EC50 value for ABTS radical-scavenging activity was 0.265 ± 0.003 mg/L. Moreover, this extract showed high iron (II) chelating ability (EC50 = 0.958 ± 0.137 mg/L), and good antioxidant activity in the cupric ion reducing activity (CUPRAC) in a concentration dependent manner (EC50 were 0.709 ± 0.002 mg/L). Additionally, this extract had the best antihemolytic activity against AAPH-induced hemolysis (EC50 = 0.090 ± 0.004 mg/L). Our study revealed that the aqueous extract of Hammada elegans Botsch, is a potential source of antioxidants which possess a high protective effect of membrane against free radical. The acute toxicity study shows no deaths in rats and no clinical signs of toxicity after administration of increasing doses of the extracts (50-1500 mg/kg bw). The anti-inflammatory effects show that all extracts significantly inhibit rat paw edema (EC50 less than 345.51 ± 0.29 mg/kg bw). Therefore, the acetonic extract (EC50 = 157.45 ± 0.33 mg/kg bw) had the more active anti-inflammatory activity than that of the standard inhibitor “Ibuprofen”. The evaluation of the antidiabetic activities by three tests shows that: in the short-term test there is no significant decrease in blood sugar in normal rats, whereas in starch-induced hyperglycemia test the aqueous extract was significantly decreases hyperglycemia (57.21 ± 1.24 mg AEAC/kg bw) when compared to all tested extracts, while in the long-term test the acetonic extract was significantly decreases hyperglycemia (9.18 ± 0.72 mg GEAC/kg bw) when compared to all tested extracts. In conclusion, this study shows that Hammada elegans Botsch extracts have good antioxidant capacities andseem to have potential therapeutic possibilities potential for the prevention and treatment of the inflammatory and diabetic effects. Its properties appear to be linked to its richness in bioactive molecules.